Deterrence and Arms Control. Issue 1 (2nd January 2019) - Lewis, Jeffrey
Abstract : The Brink: President Reagan and the Nuclear War Scare of 1983 Marc Ambinder. New York: Simon & Schuster, 2018. $27.00. 364 pp. The Control Agenda: A History of the Strategic Arms Limitation Talks Matthew J. Ambrose. Ithaca, NY: Cornell University Press, 2018. $45.00. 267 pp. North Korea, Iran, and the Challenge to International Order: A Comparative Perspective Patrick McEachern and Jaclyn O'Brien McEachern. Abingdon: Routledge, 2017. £105.00/$145.00. 178 pp. Hacking the Bomb: Cyber Threats and Nuclear Weapons Andrew Futter. Washington DC: Georgetown University Press, 2018. $29.95. 196 pp. On the Brink: Trump, Kim, and the Threat of Nuclear War Van Jackson. Cambridge and New York: Cambridge University Press, 2018. £18.99/$24.95. 236 pp.